2014
DOI: 10.1177/1077546314560041
|View full text |Cite
|
Sign up to set email alerts
|

Arithmetic solution for the axial vibration of drill string coupling with a down-the-hole hammer in rock drilling

Abstract: Down-the-hole hammer (DTH) drilling is an air hammer drilling technique designed for drilling through bedrock and features a typical drill string length of 200 m or shorter due to its technical specifications. During DTH drilling of granite-like hard rocks, the impacts of the piston-bit-rock system cause the drill string to generate severe vibration and noise pollution. In addition, the rapid wear of the button bit and drill string significantly decreases the drilling efficiency. Based on a distributed paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Meng et al solved the problem of reasonable deviation and improved drilling efficiency by using the KQC series of air hammers [12]. Bu et al analyzed the impact performance and the phenomenon of the drill string's axial forced vibration with a periodic impacting force using ANSYS software [13,14]. Depouhon et al presented a dynamical model that integrates the axial dynamics of elastic piton and drill bit and analyzed the percussive drilling system [15].…”
Section: Introductionmentioning
confidence: 99%
“…Meng et al solved the problem of reasonable deviation and improved drilling efficiency by using the KQC series of air hammers [12]. Bu et al analyzed the impact performance and the phenomenon of the drill string's axial forced vibration with a periodic impacting force using ANSYS software [13,14]. Depouhon et al presented a dynamical model that integrates the axial dynamics of elastic piton and drill bit and analyzed the percussive drilling system [15].…”
Section: Introductionmentioning
confidence: 99%
“…Ryu et al [8] developed a novel technique for micro-tunnel excavation using a multihammer drilling machine and identified the optimum operating conditions of the system. Bu et al [9,10] studied the phenomenon of the drill string's axial forced vibration with a periodic impacting force under DTH drilling in an innovative manner. Depouhon et al [11] presented a novel dynamical model to analyze the long-term response of the percussive drilling system.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of drillstring vibrations has been recognized for many years as one of the prime causes of deterioration in drilling performance, and was subjected to some investigations as reported in the literature (Khulief et al., 2008; Bu et al., 2014; Ghasemloonia et al., 2014; Kamel and Yigit, 2014; Zhu and Jing 2014; Ghasemloonia et al., 2015). Field observations based on downhole and surface vibration measurement have indicated that drillstring exhibits severe vibrations.…”
Section: Introductionmentioning
confidence: 99%